ZK-Hammer: Leaking Secrets from Zero-Knowledge Proofs via Rowhammer - Liang, Junkai; Zhang, Xin; Hu, Daqi; Shen, Qingni; Fang, Yuejian; Wu, Zhonghai (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
Zero-knowledge succinct non-interactive arguments of knowledge (zk-SNARK) schemes have been a promising technique in verified computation. Zk-SNARK schemes were designed to be mathematically secure against cryptographic attacks and it remains unclear whether they are vulnerable to fault injection attacks. In this work, we provide a positive answer by presenting ZK-Hammer, which leaks secrets from zk-SNARK schemes via Rowhammer. We incur faults in the exponentiate variables in the Quadratic Arithmetic Program (QAP) problem. Then we analyze the faulty proof using the bilinear pairing technique and manage to recover the secret. We employ a Rowhammer fault evaluation in libsnark and identify 3 CVEs.